2010
DOI: 10.1038/ijo.2010.57
|View full text |Cite
|
Sign up to set email alerts
|

The longitudinal influence of home and neighbourhood environments on children's body mass index and physical activity over 5 years: the CLAN study

Abstract: Objective: To determine the independent contributions of family and neighbourhood environments to changes in youth physical activity and body mass index (BMI) z-score over 5 years. Methods: In 2001 years at baseline) had their height and weight measured (BMI was converted to z-scores using Centers for Disease Control and Prevention reference charts; see http://www.cdc.gov/growthcharts) and moderate-to-vigorous physical activity (MVPA) assessed using accelerometers. In 2001, parents reported on the home environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
152
4
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(178 citation statements)
references
References 46 publications
10
152
4
6
Order By: Relevance
“…Children are more physically active when outdoors than indoors, 52 and children who walk or bike to school are more active than children who travel by other means. 53,54 However, other contexts, such as the indoor home 55 or school environment, [56][57][58] may also influence physical activity at early ages. The social context, including local norms about body size, is also likely to influence activity and adiposity; indeed, local norms may be responsible for our finding that living in a neighborhood with more immigrants predicts lower adiposity.…”
Section: Discussionmentioning
confidence: 99%
“…Children are more physically active when outdoors than indoors, 52 and children who walk or bike to school are more active than children who travel by other means. 53,54 However, other contexts, such as the indoor home 55 or school environment, [56][57][58] may also influence physical activity at early ages. The social context, including local norms about body size, is also likely to influence activity and adiposity; indeed, local norms may be responsible for our finding that living in a neighborhood with more immigrants predicts lower adiposity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that higher parental weight status is associated with higher adolescent weight status; this association has also been demonstrated among minority populations (Zeller et al, 2007). A small but growing evidence base also suggests that parental health behaviors, specifically parent physical activity and healthy eating, are inversely associated with youth weight status (Berge, Wall, Bauer, & Neumark-Sztainer, 2010;Crawford et al, 2010). Parent obesity, physical activity, and fruit and vegetable intake may be important predictors of youth weight status because adolescents may learn positive health behaviors by observing their parents health and health behaviors.…”
Section: Parental Limit Setting Of Sedentary Behaviors Parent Obesitmentioning
confidence: 99%
“…Earlier research suggests that these behaviours may be influenced or predicted by different factors in girls and boys (24)(25)(26)(27) . For example, two previous studies have found that parental PA behaviour was only related to PA behaviour of boys, not girls (24,25) . To our knowledge, no previous studies have examined SES as a potential moderator of correlates of EBRB in early adolescence.…”
mentioning
confidence: 99%